Extracorporeal CO2 Removal (ECCO2R): Hope or Hype? Extracorporeal CO2 Removal (ECCO2R): Hope or Hype? - Abbas, Dr Mohammad; Fakruddin, Dr Mohammad; Tabassum, Dr Shainaz; Begum, Dr Farzana (International Journal of Innovative Research in Medical Science, 2025)
Recent technological advancements have simplified the design of extracorporeal membrane oxygenation devices, paving the way for specialized devices dedicated to the targeted removal of carbon dioxide (CO2) from the body. These CO2 removal devices feature a more streamlined configuration compared to traditional extracorporeal membrane oxygenation devices, operating at lower blood flows to minimize potential complications. Experimental studies have confirmed the viability, efficacy, and safety of extracorporeal CO2 removal, showcasing its potential benefits in human subjects. Initially conceptualized as an adjunct therapy for individuals with severe acute respiratory distress syndrome, COPD, Status asthmaticus and pulmonary artery hypertension in COPD awaiting lung transplant this approach aimed to optimize protective ventilation strategies. More recently, the application of extracorporeal CO2 removal has given rise to the concept of "ULTRA-Lung protective ventilation," the complete implications of which are still under exploration. Moreover, the technique has demonstrated promising outcomes in addressing exacerbated hypercapnic respiratory failure. This review delves into the intricate details of the physiological and technical aspects of CO2 removal therapy and its various iterations. Additionally, it presents a comprehensive survey of the existing clinical evidence, illuminating the evolving potential of this innovative approach.